GoldClear® anti-acne patch: harnessing natural efficacy with modern drug delivery for acne care - Zaini, Aliff Zulkarnain; Hazizul Hasan, Mizaton; Abdul Hamid, Khuriah; Jahidin, Aisyah Hasyila; Mahamood, Maziana; Mustaffa, Mohd Faiz (Faculty of Pharmacy, 2025)
Acne vulgaris is a common skin condition that affects millions worldwide, often leading to physical discomfort and psychological distress. Conventional treatments, typically in cream or gel form, can be sticky, unpleasant, and easily washed off, which reduces effectiveness and user compliance and potentially contributes to resistance issues. In recent years, natural plant extracts have gained popularity as alternative therapeutic agents due to their safety profile and multiple bioactive properties. This study focuses on developing an anti-acne patch, GoldClear®, infused with Allamanda cathartica (golden trumpet) leaf extract. The GoldClear® extract demonstrated rich phytochemical constituents, high efficacy, low cytotoxicity, and a favourable selectivity index, ensuring safe application on the skin. Incorporating this extract into a patch allows targeted delivery, enhancing its therapeutic action and minimizing systemic exposure. The in vitro study revealed that the GoldClear® patch exhibits potent bactericidal activity against Propionibacterium acnes, a key pathogen implicated in acne development, showing effectiveness comparable to tea tree oil gel. These findings highlight the potential of GoldClear® as a natural and effective solution for acne management, offering an innovative, patient-friendly approach that leverages botanical extracts with modern drug delivery systems.